Factors Affecting the Performance of State Civil Services in Makassar City Social Services Post Covid 19 Pandemic - Darmawan Sanusi; Andi Agustang; Andi Muhammad Idkhan (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The problem discussed in this study is the State Civil Apparatus (ASN) which tends to not describe high performance due to the ability and motivation factors it has as implications of the covid-19 pandemic. Therefore, this study aims to identify and analyze the factors that affect the performance of ASN at the Makassar City Social Service after the Covid-19 pandemic. The research method used is descriptive-qualitative method. The unit of analysis in this study includes primary data sources, which are a number of data collected from 24 informants consisting of 22 structural officials and 2 staff and 1 street child who is considered representative who was chosen purposively.. Secondary data sources are sources of data obtained from the study of documents related to the research focus. The results of the study indicate that the factors that influence the performance of ASN at the Makassar City Social Service can be seen from the aspect of ASN's ability and motivation. The ability factor consists of intellectual and physical abilities. Intellectual ability shows that there are 3 sub-indicators of intellectual ability that most determine the performance of ASN, namely, numerical intelligence, verbal comprehension and spatial visualization.